2017
DOI: 10.1021/acs.jpcb.7b04271
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Relaxation of the Backbone and Base Modes in LacDNA Complexes by UV Resonance Raman Spectroscopy

Abstract: Vibrational band shape analysis through time correlation function concept is widely used to obtain experimental information on the molecular dynamics of medium-size molecules in different environments. Interesting details are revealed by extending this technique to biomolecules such as functional groups of the nucleic acids in media approaching the physiological conditions. In this work a study into the UV resonance Raman (UVRR) vibrational half bandwidths of functional groups in LacDNA, upon lowering the pH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The experimental set-up used for HRS was already described elsewhere 58 . The laser system (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental set-up used for HRS was already described elsewhere 58 . The laser system (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the fwhm's of calf-thymus DNA Raman bands revealed their sensitivity to pH, as well as to the presence and concentration of different metal cations [13]. Besides, our group investigated the vibrational relaxation of a 22-mer duplex DNA, as probed with UVRR spectroscopy [14]. Resonance Raman spectroscopy (RRS) is a useful technique employed to obtain experimental data on molecular relaxation dynamics [15].…”
Section: *Email: Cmuntean@itim-cjro; Ioanbratu@itim-cjro # Authorsmentioning
confidence: 99%
“…The UV resonance Raman measurements were done at the University of Osnabrück, Osnabrück, Germany. Continuous wave Raman equipment described in detail elsewhere [14,21] was employed for recording the UVRR spectra. All UV resonance Raman profiles of dAMP molecules were registered in the same experimental conditions.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation